2019
DOI: 10.1097/mnm.0000000000001104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between single-photon emission computed tomography/computed tomography and ultrasound in preoperative detection of parathyroid adenoma: retrospective review of an institutional experience

Abstract: Objective The aim of this study was to evaluate the accuracy of technetium- 99m-methoxyisobutylisonitrile (99mTc-MIBI) single-photon emission computed tomography/computed tomography (SPECT/CT) and ultrasound in preoperative localization of single parathyroid adenomas (PTAs) in patients with primary hyperparathyroidism (pHPT) who would be suitable for minimally invasive parathyroidectomy (MIP). Methods A retrospective study of 143 consecutive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Of 119 studies, 48 were performed in a prospective manner. The sensitivity on a per-patient–based analysis was available in 84 studies (Table 1), whereas the sensitivity on a per-lesion–based analysis was available in 39 studies (Table 2). Of the 84 patient-based studies, 47 were reported before 2009, and 37 were reported after 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Of 119 studies, 48 were performed in a prospective manner. The sensitivity on a per-patient–based analysis was available in 84 studies (Table 1), whereas the sensitivity on a per-lesion–based analysis was available in 39 studies (Table 2). Of the 84 patient-based studies, 47 were reported before 2009, and 37 were reported after 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound has been shown to perform poorly for cases of ectopic adenomas, again highlighting the use of SPECT/CT for these patients. 7,12 As time progressed following the introduction of the SPECT/CT scanner, investigation pathways and imaging requests from clinicians demonstrated a shift with SPECT/ CT being requested as the primary imaging modality (Table 4). Our suggested pathway for the investigation of parathyroid adenomas may be to start with SPECT/CT scan and proceed to an ultrasound or 4D CT in equivocal or negative cases to confirm the SPECT/CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound has the additional advantages of being noninvasive, lacking radiation exposure and being quick to perform, although accuracy of results is dependent on the skill of the operator. Ultrasound has been shown to perform poorly for cases of ectopic adenomas, again highlighting the use of SPECT/CT for these patients 7,12 …”
Section: Discussionmentioning
confidence: 99%
“…Inabnet et al [16] implied systematic surgical exploration rather than minimal procedure since preoperative sestamibi screening and ultrasound could not fully localize. Okudan et al [17] reported that computed tomography was more accurate than ultrasound in determining preoperative single adenoma in with a patient with primary hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%